Determinación del Incremento Medio Anual de Tectona grandis L. f. (teca) proveniente de cinco fuentes semilleras en el cantón Quinindé, provincia de Esmeraldas - Luna Loor, Ginger Karem (2021)
The growth of a tree is rationed with age, all species change during their development due to their endogenous growth and exogenous limitations produced by the environment, individuals with optimal phenotypic characteristics are destined to increase and improve the production of seeds in quality and amount. Therefore, the present study aimed to determine the mean annual increase of Tectona grandis L. f. (teak) from five seed sources in the Quinindé canton, Esmeraldas province. The seed sources of T. grandis used are; Pilangosta Broadleaf Guanacaste Lot 1 (Costa Rica), Pilangosta Broadleaf Guanacaste Lot 2 (Costa Rica), Santa Cruz Guanacaste Lot 059/966 (Costa Rica), Parrita Quepos Puntarenas (Costa Rica) and Quevedo province of Los Ríos (Ecuador) . The research was carried out on the premises of the Instituto Tecnologico Superior de Quininde located in the Quinindé canton, Esmeraldas province. A completely randomized design with five treatments and three repetitions was used. The test consisted of 15 sampling units of 15 x 15 (225 m2), five for each repetition. The variables evaluated were diameter, basal area, total height, commercial height, total volume and commercial volume, and based on these variables the AMI was calculated, in addition, a Tukey test was carried out to observe whether or not there were significant statistical differences between the variables of each origin. At 21 years of age from the T. grandis plantation, it was determined that there is no significant difference between the treatments for the variables of diameter, total height, commercial height, basal area, total volume and commercial volume according to the Tukey test (p > 0.05), being the origin of Quevedo province of Los Ríos that presented a better average in diameter with 1.37 cm, total height with 1.22 m, commercial height with 0.59 m, in the same way the basal area per hectare that resulted in 26.22 m2, total volume per hectare with 486.89 m3 and with regard to the variable commercial volume per hectare, there was a difference of 240.26 m3 for the same treatment. Keywords: Treatments, increase, seed sources, repetitions, Tectona grandis.